Sovereignty on the Northern Plains: Indian, European, American and Canadian Claims - McNeil, Kent (Osgoode Digital Commons, 2000)
The Colonization of North America by Europeans raised fundamental issues about the status and rights of the original inhabitants of this continent. Were the Indian and Inuit peoples sovereign nations, with territorial rights equivalent to those of the European sovereigns in the so-called Old World? Did they have rights to the soil on a par with those of landowners in Britain, France, or Spain? If they were sovereign nations with territorial or land rights, what impact did European colonization have on them? Even today, these questions have not been completely resolved. In Canada, for example, as recently as 1997 the Supreme Court left open the question of whether the Indian and Inuit peoples have an inherent right of self-government that survived European colonization. At the same time, the Court decided that those peoples do have a right of exclusive use and occupation of their traditional lands, if they can prove they were in exclusive occupation of them at the time of assertion of European sovereignty. This means that the question of when sovereignty was acquired can have profound contemporary significance for the Indian and Inuit peoples of Canada. In the United States, these issues were addressed by the Supreme Court in the 1820s and 1830s. However, the discussion in this article will show that these early decisions are often misinterpreted or ignored in the context of acquisition of European sovereignty. All too often, it is assumed that the European nations were able to acquire sovereignty over the territories of the Indian and Inuit nations without their consent, and without actually taking possession and establishing effective control. This article will challenge this assumption, and reassess the manner and time of acquisition of European sovereignty in North America, by focusing on the geographical region of the Northern Plains. Copyright Journal of the West ©2000, reprinted with permission of ABC-CLIO.